PENERAPAN METODE MULTIDIMENSIONAL SCALING (MDS) DALAM PERENCANAAN FORMULASI STRATEGI PEMASARAN SUPERMARKET HERO MALANG - Santoso, Sugeng (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
Customer value is customer's believeing to the most important atributes of supermarket. Those are all about marketing mix atributes such as cost, product, distribution, and promotion. Customer's value can be found with implementing Multidimensional Scaling Method that spreading questionnaires and interviewing to have initial data.This research used Multidimensional Scaling Method to know customer's demand to supermarkets. This can be used as a beginning standart in marketing strategy planning. This method result a perception map that drawing challanging situation among the supermarket that viewed from marketing mix atributes.The result of analysis conclude that demand or the most customer's important atributes for choosing supermarket is cost atribute and distribution. In Hero Supermarket, customer's demand is in product atribute that it's items are good quality product and variety that Hero standed in Kuadran I. To get customers I market segmentation to marketing strategy formulation is : if in area CI, Hero supermarket have a competition with Alfa Supermarket, so that should stress it's strategy in cost atribute. It's also in area III, Hero Supermarket and Ratu Supermarket have a competition in cost atribute. And in area IV, a competition happen among Hero, Mitra, and Matahari departement store in distribution and promotion atribute.